(untitled) (Hanoi, 1991)
This English edition is a translation of the Legal writings on foreign investment in Viet Nam
Keywords: Investments, Foreign,Đầu tư, nước ngoài; Law and legislation,Luật và pháp chế; Vietnam,Việt Nam